Konsep Dasar Transmisi Tenaga Listrik: Klasifikasi, Komponen Serta Gangguannya - Aan Sumiyati; Putri Shabira Rahman; Muhammad Habil Cahaya Gusti; Gregorius Diera Arnandi Melkior; Johan Hidayat; Didik Aribowo (Fakultas Teknik UMRI, 2024)
Electric transmission lines have a vital role as a bridge between electrical energy resources and distribution points to final consumers. In classifying transmissions, aspects such as the installation technology used, the voltage level applied, and the physical channel distance are very influential in ensuring overall operational system efficiency. However, this transmission system does not require various challenges that need to be overcome, such as power losses that can occur during the transmission process, technical problems that can arise at any time, and the risk of too much dependence on main connected lines. Dramatic events such as mass power outages in the Java-Bali region in 2019 show how important it is to increase infrastructure capacity, increasing regular maintenance programs. This research uses a qualitative approach through a literature analysis study which is used to explore issues related to the electricity transmission system in Indonesia, with the research results underlining the need for increased supervision and policy crisis management as well as carrying out stricter maintenance to maximize electricity availability effectively in the future.